Diary of a wimpy kid : double down Vol.11 - Kinney, Jeff (New York : Amulet Books, 2016)
Greg Heffley's mom wants him to take a break from video games while Halloween approaches and he comes up with an idea to make a movie.
Keywords: Diaries -- Fiction; Family life -- Fiction; Motion pictures -- Production and direction -- Fiction; Halloween -- Fiction; Humorous stories